Extra-Cranial Carotid Artery Stenosis: An Objective Analysis of the Available Evidence - Abbott, Anne L. (Frontiers in Neurology, 2022)
Background and Purpose: Carotid stenosis is arterial disease narrowing of the origin of the internal carotid artery (main brain artery). Knowing how to best manage this is imperative because it is common in older people and an important cause of stroke. Inappropriately high expectations have grown regarding the value of carotid artery procedures, such as surgery (endarterectomy) and stenting, for lowering the stroke risk associated with carotid stenosis. Meanwhile, the improving and predominant value of medical intervention (lifestyle coaching and medication) continues to be underappreciated. Methods and Results: This article aims to be an objective presentation and discussion of the scientific literature critical for decision making when the primary goal is to optimise patient outcome. This compilation follows from many years of author scrutiny to separate fact from fiction. Common sense conclusions are drawn from factual statements backed original citations. Detailed research methodology is given in cited papers. This article has been written in plain language given the importance of the general public understanding this topic. Issues covered include key terminology, the economic impact of carotid stenosis and procedural management. There is a summary of the evidence-base regarding the efficacy and safety of procedural and medical (noninvasive) interventions for both asymptomatic and symptomatic patients. Conclusions are drawn with respect to current best management and research priorities. Several ‘furphies’ (misconceptions) are exposed that are commonly used to make carotid stenting and endarterectomy outcomes appear similar. Ongoing randomised trials are mentioned and why they are unlikely to identify a routine practice indication for carotid artery procedures. There is a discussion of relevant worldwide guidelines regarding carotid artery procedures, including how they should be improved. There is an outline of systematic changes that are resulting in better application of the evidence-base. Conclusion: The cornerstone of stroke prevention is medical intervention given it is non-invasive and protects against all arterial disease complications in all at risk. The ‘big’ question is, does a carotid artery procedure add patient benefit in the modern era and, if so, for whom?